2021
DOI: 10.1136/bmjresp-2020-000845
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnoea is a risk factor for severe COVID-19

Abstract: BackgroundObstructive sleep apnoea (OSA) is associated with higher body mass index (BMI), diabetes, older age and male gender, which are all risk factors for severe COVID-19.We aimed to study if OSA is an independent risk factor for COVID-19 infection or for severe COVID-19.MethodsOSA diagnosis and COVID-19 infection were extracted from the hospital discharge, causes of death and infectious diseases registries in individuals who participated in the FinnGen study (n=260 405). Severe COVID-19 was defined as COVI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 19 publications
6
74
1
5
Order By: Relevance
“…However, our study involved general population using an online platform. The participants in our study were younger, with fewer comorbidities, such as hypertension and COPD, than previous studies on COVID-19-hospitalized patients [5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…However, our study involved general population using an online platform. The participants in our study were younger, with fewer comorbidities, such as hypertension and COPD, than previous studies on COVID-19-hospitalized patients [5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, our study showed that participants with the following characteristics-high risk of OSA, being male, having diabetes, and having depression-were two to three times more likely to have been hospitalized or to require ICU treatment due to COVID-19. To the best of our knowledge, our study is the first in the literature focusing on hitherto undiagnosed OSA by using the STOP questionnaire and the risk of COVID-19, whereas previous studies examined COVID-19hospitalized patients with physician-diagnosed OSA [5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations